2002
DOI: 10.1128/jb.184.12.3368-3376.2002
|View full text |Cite
|
Sign up to set email alerts
|

Chlorobium tepidum Mutant Lacking Bacteriochlorophyll c Made by Inactivation of the bchK Gene, Encoding Bacteriochlorophyll c Synthase

Abstract: The gene encoding bacteriochlorophyll (BChl) c synthase was identified by insertional inactivation in the photosynthetic green sulfur bacterium Chlorobium tepidum and was named bchK. The bchK mutant of C. tepidum was rusty-orange in color and completely lacked BChl c. Because of the absence of the BChl c antenna, the mutant grew about seven times slower than the wild type at light intensities that were limiting to the wild type (<90 mol m ؊2 s ؊1 ). Various pheophorbides, which probably represent precursors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 45 publications
5
77
0
Order By: Relevance
“…The solvent system for analysis of all strains was modified from the previously described system (73). Solvent B was 50% methanol, 30% ethyl acetate, and 20% acetonitrile, and solvent A consisted of water:methanol:acetonitrile (62.5:21:16.5) containing 10 mM ammonium acetate.…”
Section: Inactivation Of Ct0456mentioning
confidence: 99%
“…The solvent system for analysis of all strains was modified from the previously described system (73). Solvent B was 50% methanol, 30% ethyl acetate, and 20% acetonitrile, and solvent A consisted of water:methanol:acetonitrile (62.5:21:16.5) containing 10 mM ammonium acetate.…”
Section: Inactivation Of Ct0456mentioning
confidence: 99%
“…3 In contrast, the bchJ::aadA cells were orange in color, which suggested that these cells had a severely reduced BChl c content (see Refs. 19). The whole cell absorption spectrum of the mutant and wild-type cells confirmed this observation (Fig.…”
Section: Hplc and Hplc-ms Of Chls In The Ct1063mentioning
confidence: 99%
“…2, A and B). The resulting plasmids were linearized by digestion with AhdI and used to transform wild-type C. tepidum cells as described (19). Segregation of the mutants was confirmed by PCR as described (19) (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the enzymes responsible for adding the esterifying alcohols to Chls and BChls show considerable specificity for the (B)Chlide substrate but usually have broader specificity for the esterifying alcohol (20,(51)(52)(53). In C. tepidum BchK is responsible for the addition of the farnesyl tail to BChl c, and ChlG and BchG add phytadienol and phytol to Chl a and BChl a, respectively (20). A comparative analysis of the genomes of GSB shows that all have at least three esterifying enzymes: BchK, ChlG, and BchG.…”
Section: Discussionmentioning
confidence: 99%
“…These methylation homologs are then hydroxylated at C-3 1 by BchF or BchV to produce bacteriochlorophyllide (BChlide) d (21,(27)(28)(29), and in BChl c-producing strains, they are subsequently methylated by BchU at C-20 to produce BChlide c homologs (12,30,31). Finally, the BChlide c or BChlide d homologs are esterified with farnesol pyrophosphate by BchK to produce BChl c or BChl d homologs with differing numbers of methyl groups (20). The methylation reactions catalyzed by BchU, BchQ, and BchR help to tune the absorption properties of BChl c, d, and e in chlorosomes and also lead to inhomogeneous broadening of the nearinfrared absorption band of aggregated BChls in chlorosomes (12,17,18).…”
mentioning
confidence: 99%